Réponses

  • Utilisateur Brainly
2013-02-11T15:11:52+01:00
(2x -3) (x+2) (x-1) = 0. 3x = 0-2+3-2+1 X = 0./3. X
Meilleure réponse !
2013-02-11T15:34:22+01:00

développement : 

 

(2x-3)(x+2)(x-1)

(2x*x+2x*2-3*x-3*2)(x-1)

(2x²+4x-3x-6)(x-1)

(2x²+x-6)(x-1)

2x²*x+2x²*(-1)+4x*x+4x*(-1)-3x*x-3x*(-1)-6*x-6*(-1)

2x³-2x²+4x²-4x-3x²+3x-6x+6

2x³-x²-7x+6

 

les trois solutions

 

2x-3=0

2x=0+3

2x=3

x=3/2

x=1.5

 

x+2=0

x=0-2

x=-2

 

x-1=0

x=0+1

x=1

 

les 3 solutions sont donc  1.5 ; -2 ; 1